Special economic zones in the Philippines effective or ineffective - Marcelo, Ronniel R.; Jimenez, Khim N.; Reside, Renato Jr. E. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
We have studied the effects of the status quo special economic zone (SEZ) incentive system in the Philippines in order to add to the discourse on the proposals to rationalize fiscal incentives in the country. Taking into consideration that the amount of employment and values of investment in a province or city may be spatially dependent, spatial econometrics modeling was used to estimate the effect of SEZ employment and investment on the total amount of employment and total value of investments for every province or city in the Philippines. A cross section dataset for total employment and investment, along with their standard determinants, was interpolated for the year 2015. To evaluate the effects of the SEZ incentive system, regressing the data coming from the Philippine Economic Zone Authority (PEZA) is acceptable since it is the most dominant investment promotion agency managing economic zones in the country. Therefore, the provincial level data of PEZA direct employment and PEZA approved investments for the year 2015, along with the standard determinants of employment and investments, were regressed on the provincial level data on total employment and total investments per province in the country. A spatial weight matrix which assumes a 350_kilometer neighborhood among provinces and cities was also used in the regression. Through the study, we have proven that while SEZ investment incentives are ineffective, SEZ employment does not only crowds out to areas outside the economic zones, but it also positively affects neighboring provinces or cities in very significant terms. Decreasing the distance for neighborhood assumption from 350 to 300 kilometers does not change the conclusions of our study, since there has been no theoretical basis to assume that the significance of estimates are highly sensitive to the distance assumed for neighborhood.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Economic zoning -- Philippines; Employment (Economic theory).; Investments -- Philippines; Special Economic Zone (SEZ).